PENENTUAN KADAR KALIUM (K) DAN KALSIUM (Ca) DALAM LABU SIAM (Sechium Edule) SERTA PENGARUH TEMPAT TUMBUHNYA (Determination of Potassium (K) and Calcium (Ca) Content in Chayote (Sechium Edule) and The Effects With its Growth Soil) - Cicik Fitriani, Ni Luh; Walanda, Daud K; Rahman, Nurdin (Jurnal Akademika Kimia, 2012)
Chayote (sechiumeaite) is an alternative source of vegetable which is consumed largely by the community. For that reason, the research was conducted to determine the content of potassium (K) and calcium (Ca) as wll as its relation to the growth soil. The method of this research is laboratory experiments by using atomic absorption spectrometry. The result shows that the content of potassium in Palolo’s chayote meat is 134.35 mg/100 g, skin and fruit meat is 269.10 mg/100 g, and in the ground is 34.02 mg/100 g. However, in Kebun Kopi’s pumpkin, the content of potassium (K) is 177.42 mg/100 g in its fruit meat, 298.35 mg/100 g in its skin and fruit meat, and 88.02 mg/100 g in the soil. On the other hands the content of calcium obtained as follows: in Palolo’s chayote meat is 38.53 mg/100 g, in the skin and fruit meat is 55.865 mg/100 g, and in the soil is 32.72 mg/100 g. In the area of Kebun Kopi’s chayote meat is 20.535mg/100 g, in the skin and fruit meat is 30.605 mg/100 g, and in the soil is 7.682 mg/100 g. Therefore, the content of potassium and calcium obtained is higher than in the literature.